2017
DOI: 10.1177/2325967117708190
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Peripheral Passive Rotation Stabilizers of the Knee With Intact Collateral and Cruciate Ligaments: A Biomechanical Study

Abstract: Background:A subset of patients have clinical internal and/or external knee rotational instability despite no apparent injury to the cruciate or collateral ligaments.Purpose/Hypothesis:The purpose of this study was to assess the effect of sequentially cutting the posterolateral, anterolateral, posteromedial, and anteromedial structures of the knee on rotational stability in the setting of intact cruciate and collateral ligaments. It was hypothesized that cutting of the iliotibial band (ITB), anterolateral liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Other studies have also indicated the importance of the ITB in restraining internal rotation. 11,13,28 A recent study by Vap et al 27 demonstrated the relevant roles of the distal ITB and the ALL–lateral capsule complex. When the distal ITB was sectioned before the ALL–lateral capsule complex, the observed changes were greater than those observed when the ALL–lateral capsule complex was sectioned before the distal ITB.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also indicated the importance of the ITB in restraining internal rotation. 11,13,28 A recent study by Vap et al 27 demonstrated the relevant roles of the distal ITB and the ALL–lateral capsule complex. When the distal ITB was sectioned before the ALL–lateral capsule complex, the observed changes were greater than those observed when the ALL–lateral capsule complex was sectioned before the distal ITB.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,12,36,44 Sectioning of the ALL in biomechanical cadaveric studies resulted in greater rotational laxity in both the ACL-deficient knee 43 and the ACL-intact knee. 51 Augmentation of ACLR with an extra-articular tenodesis was shown to decrease rotational laxity and residual pivot shift. 12,13 Recently published clinical results demonstrated reduced failure of combined ACLR and ALLR as compared with isolated ACLR, which may be attributed to biomechanical load-sharing properties of the ALL graft.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors’ (PWW, VM) approach, the posterior drawer test is performed in internal, neutral, and external rotation of the tibia to assess additional injuries of the peripheral capsuloligamentous structures since biomechanical studies have shown that the structures of the PMC and PLC are secondary restraints against internal and external tibial torque, respectively [ 30 , 35 , 54 , 58 , 70 , 75 ]. Furthermore, all PCL injuries are classified according to the classifications proposed by the American Medical Association [ 60 ], Hughston and colleagues [ 27 , 28 ], and Harner et al [ 20 ].…”
Section: Anatomymentioning
confidence: 99%